Social Media Intervention to Improve University Students’ Well-Being: A Self-Determination Approach - Ngu, Ik Ying (Journal of Contemporary Issues in Media & Communication (JCIMC), 2025)
The debate on the effect of social media use on students’ psychological well-being has attracted much attention and interest around the development of social media interventions in higher education. This study investigated university students’ interactions with social media and its effect on their well-being. An intervention was designed to support and improve students’ well-being. Guided by Ryan and Deci’s (2000) Self-Determination Theory (SDT), this study aimed to assess associations between social media use and individuals’ intrinsic motivation and psychological needs in the academic context. A focus-group qualitative approach was used to collect data among university students and explore the relationship between social media use and the way they cope with stress in their first year of undergraduate study. Results showed high social media use among students who experienced stress, but the effect of social media on students’ well-being varies between their psychological needs of autonomy, competence, and relatedness. The study combined SDT and basic psychological needs to address the issue. We conclude that individual differences play an important role in social media use. This study used inductive coding approaches and offered a comprehensive approach to conceptualise students’ social media use and well-being. We propose theoretically grounded design features that can identify stressors among students, reflect their psychological needs, and propose strategies that can be used to cope with social media. Many current educational policies and practices fail to recognise the importance of psychological needs satisfaction in learning contexts, despite substantial evidence, and therefore create a gap that this study aims to close. This study proves that individuals’ consumption of social media does not solely justify their stressors and the effects on their well-being, but the autonomous form of motivations for specific social media use and psychological needs matter.